From blood transfusion to patient blood management: a new paradigm for patient care and cost assessment of blood transfusion practice - Leahy, M.; Mukhtar, Syed Aqif (Blackwell Publishing, 2012)
The ageing population in developed countries, including Australia, is putting increasing demands on blood transfusion services. With a falling donor pool there is likely to be a shortage of blood and blood products in the next 20 to 30 years unless there are significant changes in medical practice. The National Health and Medical Research Council/Australasian Society of Blood Transfusion Clinical Practice Guidelines on the Use of Blood Components from 2001 are being redeveloped by the National Health and Medical Research Council/Australian and New Zealand Society of Blood Transfusion as evidence-based patient-focused Patient Blood Management guidelines with the aim of improving patient outcomes by reducing inappropriate blood and blood product use and targeting therapies for improving the management of anaemia and coagulopathies.